Classification of fracture neck of femur - Bikas Sahoo; Alok C Agrawal; Bikram K Kar; Harshal Sakale; Sandeep K Yadav; Sameer Mittal (Journal of Orthopaedic Diseases and Traumatology, 2018)
There are numerous classification systems for fracture neck of femur in adults. A fracture classification is proposed either for taxonomical purpose, characterization, guiding intervention, or predicting outcomes of intervention. The classifications described in this chapter are needed to decide on choice of implant, stability, acceptability of reduction, vascularity and long term prognosis.